Evaluation of Institutional Development : Case on Private Forest Farmer Group in Sumbawa Regency (Komunitas, 2019)
Although a large number of studies have been conducted to evaluate the success of farmer groups, a comprehensive evaluations starting from group formation process has not been carried out much.  This research rates the success of farmer groups as a vehicle to improve the livelihoods of farmers in the area of Management Unit of Production Forest (KPHP) of Puncak Ngengas-Batu Lanteh, Sumbawa. The success was measured by evaluating three roles of farmer groups namely,  a) class for learning, b) forum for collaboration, and c) unit for production. This research was conducted in two periods, i.e. on April 2016 and April 2017. The sample consisted of 20 forest farmers selected purposively, the data were collected through interviews and focus group discussion techniques and analysed descriptively. This study revealed that the roles scale of farmer groups as class for learning and as a forum for collaboration were categorized as low level, while as a unit for production was categorized as moderate level. These categories show that in general the farmer group had not succeeded in carrying out its function as a class for learning, and as a vehicle for collaboration, except as a unit for production. This weak condition was utilized by middlemen to take advantages from marketing activity by controlling forest product prices.  The Kanada farmer group was categorized in the beginner group which needs 75 % intervention from outsider such as continual mentoring by counsellors to grow the attitude from working alone to working together in a group.